Retracted: Spider aggressiveness determines the bidirectional consequences of host–inquiline interactions. (4th November 2013) - Keiser, Carl N; Pruitt, Jonathan N
Abstract: Individual behavioral variation (aka behavioral types [BTs]) can alter the nature of species interactions. Here, we explore the performance consequences of behavioral variation in heterospecific dyads of the social spider Anelosimus studiosus and two of its most common inquilines ( Larinioides cornutus and Theridion murarium ). We determined the BTs of A. studiosus (docile vs. aggressive), determined the aggressiveness of their inquilines, and released dyads in the field for 40 days. We assessed the performance of A. studiosus and its inquilines using egg case mass and change in body mass, respectively. In the absence of inquilines, we found that aggressive A. studiosus outperformed dociles, however docile A. studiosus outperformed aggressives in the presence of inquilines. Aggression in T. murarium had a large effect on A. studiosus fecundity and its own performance, though this trend was not observed in L. cornutus . The performance of host and inquiline was simultaneously maximized when dyads were composed of opposing BTs: docile A. studiosus with aggressive T. murarium and vice versa. Thus, our data demonstrate bidirectional impacts of behavioral variation in a host–inquiline interaction and reveal that the traits that yield the greatest success in one species may depend on the representation of traits in another associated species.